2011
DOI: 10.1055/s-0031-1287841
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resting Metabolic Rate in Girls with Rett Syndrome Compared to Girls with Developmental Disabilities

Abstract: The aim of this study was to determine the body composition and resting metabolic rate (RMR) of girls with Rett syndrome (RS) (n=15) and to compare them with an equally handicapped group of girls with developmental disabilities (DD) (n=13). Body composition was measured by bioelectrical impedance analysis and RMR  -  the amount of energy expended while at rest  -  by indirect calorimetry. Weight, height, body mass index (BMI), BMI percentiles and food intake were all measured and calculated by standardized pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
6
0
1
Order By: Relevance
“…Altered energy balance and metabolic measures have been observed in human RTT females (26)(27)(28). While dietary energy intake and fecal fat loss did not differ between RTT and controls, metabolic rates during sleep and quiet awake were significantly lower (26) and morning levels of leptin and adiponectin were elevated in RTT (17).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Altered energy balance and metabolic measures have been observed in human RTT females (26)(27)(28). While dietary energy intake and fecal fat loss did not differ between RTT and controls, metabolic rates during sleep and quiet awake were significantly lower (26) and morning levels of leptin and adiponectin were elevated in RTT (17).…”
Section: Discussionmentioning
confidence: 89%
“…Metabolic dysfunctions are observed in RTT patients and mouse models, but whether these are consequences of inflammation or more directly mediated by MECP2, mutation is currently unknown. While RTT girls are generally not obese, perhaps due to the inability to self-feed, they have elevated morning leptin and adiponectin serum levels (17) as well as alterations in energy balance (26)(27)(28). Furthermore, RTT has significant commonalities with mitochondrial disorders, including elevated lactate and pyruvate in blood and cerebral spinal fluid (29), as well as markers of oxidative damage (30) that are also seen in mouse models (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…32 We found that despite persistent microcephaly, preserved somatic growth occurs in 45% of girls with RTT and is associated with better development and lower seizure, scoliosis, and RTT behavior burden, contradicting dogma that "proportional" microcephaly conveys a protective effect. The resting metabolic rate is higher in patients with RTT than in those with other developmental disabilities, 33 and intensive nutritional therapy improves growth outcomes. These findings suggest both that growth is an important outcome for clinical trials and that improved nutrition could moderate the association between growth and development.…”
Section: Figure 1 Height and Weight In Unaffected Children (Orange) Amentioning
confidence: 99%
“…After this first sign of growth retardation, poor weight gain and height growth follows in the majority. The pathophysiology behind this global growth retardation remains unclear, but some of it may be explained by an increased resting metabolic rate, in combination with more feeding difficulties in girls with RTT compared to controls with equivalent developmental disorders (Isaacs et al, 2003;Platte et al, 2011).…”
Section: Growthmentioning
confidence: 99%